Incorporating Digital Corpus Analysis Technology into English for Academic Purposes (EAP) Lesson Design for the Sri Lankan Tertiary Context: A Self-experimentation by a ‘Novice’ - Hussain, Zareena D. (Advances in Technology, 2021)
This paper reports on an observational case study conducted to investigate the possibilities available to language teachers, non-expert, or novice in corpus analysis, in integrating corpus analysis technology to design language learning activities. Despite the availability of corpus analysis technology and large amounts of studies in corpus analysis of texts, studies on corpus-based language teaching and learning, development of language teaching-learning material incorporating corpus analysis technology and techniques by teachers who are non-experts in the field of corpus analysis for classroom teaching has remained an exception. This paper records the personal experience of the researcher as a language practitioner using corpus analysis technology in designing teaching learning material to achieve the objectives of a language course for undergraduates of low English proficiency (LEP) studying in an English medium instruction (EMI) context. Although this exercise posed challenges for the language teacher who is a ‘non-expert’ to the field, the researcher documents its positive and promising outcomes as proof to support more extensive ‘non-expert’ teacher-driven, student-participatory corpus based English language learning methodologies.